"Look with thine ears": Why Writing Is Syllable-based. Issue 1 (2nd January 2023) - Daniels, Peter T.
Abstract : Writing, both ancient and modern, originates de novo only when the language written is syllabically organized, because only there does the most salient unit of speech, the syllable, correspond with the most salient unit of language, the morpheme, thus bringing a sound sufficiently to consciousness that a pictograph for the item named by the morpheme can be recognized as also representing its sound – so that it can be transferred to represent the meaning of another morpheme of the same or similar sound (the "rebus principle"). Why is the syllable the most salient unit of speech? Phoneticians cannot agree on what people recognize when counting or manipulating syllables. Phoneticians can, though, specify what the speech organs do during speech production – the configurations of lips, tongue, larynx, pharynx, and airstream closures that result in the perceived sounds of speech ("consonants" and "vowels"). Phoneticians also recognize "features" whose durations do not necessarily correspond with those of the "segments" that constitute morphemes. Yet it is neither segments nor features that are recorded in earliest writing. An answer is found in the typology of writing systems, the ways the sounds of language are treated by grammarians and linguists ancient and modern, and the ways devised for children to learn to read.